"Now everyone can fly"? Scheduled airline services to secondary cities in Southeast Asia. (June 2016) - Bowen, John T.
Abstract: Since the late 1990s, almost no world region has experienced faster air traffic growth than Southeast Asia. Much of that growth is attributable to new low-cost carriers (LCCs), which collectively accounted for nearly half of scheduled airline capacity on routes from Southeast Asian cities in 2013. Yet despite the expansion of traffic and the proliferation of carriers, airline traffic remains strongly concentrated in the key hubs of Bangkok, Singapore, Jakarta, Kuala Lumpur, Ho Chi Minh City, and Manila. Similarly, trunk routes, defined as sectors with more than 0.01 percent of global airline capacity, continue to account for 54 percent of all seat capacity in the region. LCCs have helped to perpetuate these imbalances as budget airlines like AirAsia have disproportionately favored already well-served markets. Such patterns are important because aviation plays an outsized role in Southeast Asian intercity transportation and in its economic development. The analyses reported here indicate that while the growth of aviation since the late 1990s has been impressive, that growth so far has not done much to improve Southeast Asia's entrenched patterns of spatial inequality. Highlights: Recently, Southeast Asia has been among world's growing fastest airline markets. Low-cost carriers (LCCs) are more important in Southeast Asia than in other world regions. Airline capacity is strongly concentrated in the region's main hubs and on trunk routes. LCCs in Southeast Asia have favored well-established routes and markets.